At IDNLearn.com, find answers to your most pressing questions from experts and enthusiasts alike. Find in-depth and trustworthy answers to all your questions from our experienced community members.
Sagot :
Answer:
y = -7x+3
Step-by-step explanation:
We can write the function as
y = (3-x) / 7
To find the inverse of this function we have to do 2 things
a. change x with y and y with x and
b. find the y
a. y = (3-x) / 7, change x with y and y with x
x = (3-y) / 7, multiply both sides by 7
b. 7x = 3-y, subtract 3 from both sides
7x-3 = -y, multiply both sides by -1
-7x+3 = y
The inverse function of
f(x) = (3-x)/7 is [tex]f^{-1} (x) = -7x + 3[/tex]
Your engagement is important to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. Thank you for choosing IDNLearn.com. We’re committed to providing accurate answers, so visit us again soon.